Essential Skills And Training Provisions For Building Project Stakeholders In Palestine - Enshassi, Adnan; Mohamed, Sherif; Ekarriri, Alaá (Penerbit Universiti Sains Malaysia, 2009)
The primary aim of this paper is to identify the skills that both construction clients and contractors identify as critical to improving the building sector’s overall productivity in the Gaza Strip, Palestine. Through a comprehensive questionnaire targeting key project stakeholders (namely, clients and contractors), this paper also evaluates the factors affecting skills upgrade and the continuity of training approaches currently used in this sector. Mentoring appears to be the preferred training approach for clients and contractors alike. According to respondents, decision-making, problem solving and goal setting skills are highly critical. Furthermore, conventional face-to-face meetings were identified as the most suitable communication channel to obtain and exchange project information. Staff self-interest and willingness to upgrade their skills were ranked as the most important factors influencing the effectiveness of the professional training process. Based on the study findings, the paper concludes with a set of practical recommendations.